What's Wrong with Risk?. (7th February 2019) - Parr, Tom; Slavny, Adam
Abstract : Imposing pure risks—risks that do not materialise into harm—is sometimes wrong. The Harm Account explains this wrongness by claiming that pure risks are harms. By contrast, The Autonomy Account claims that pure risks impede autonomy. We develop two objections to these influential accounts. The Separation Objection proceeds from the observation that, if it is wrong to v then it is sometimes wrong to risk v ‐ing. The intuitive plausibility of this claim does not depend on any account of the facts that ground moral wrongness. This suggests a close relationship between the factors that make an act wrong and the factors that make risking that act wrong, which both accounts fail to recognise. The Determinism Objection holds that both accounts fail to explain the wrongness of pure risks in a deterministic world. We then develop an alternative—The Buck‐Passing Account —that withstands both objections.